Stereotyping of citizens in an expatriate‐dominated labour market: Implications for workforce localisation policy - Al‐Waqfi, Mohammed; Forstenlechner, Ingo (Employee relations, 2010)
Purpose - Even though initiatives to increase the participation of citizens in the workforce have been in place for more than a decade in the United Arab Emirates (UAE), the results are not impressive. Citizens' workforce participation - it is argued in the literature - is hindered by structural as well as attitudinal concerns. A key concern of this paper is to explore stereotypes which - as anecdotal evidence in the literature suggests - are a key hindrance to successful localisation. Design/methodology/approach - A survey was completed by 310 expatriates and citizens. Exploratory factor analysis was used to understand the key factors describing how UAE citizens are perceived and stereotyped and ANOVA analyses were used to understand the determinants of such perceptions. Findings - Findings confirm the general belief that Emiratis are negatively stereotyped by expatriates in the UAE labour market. Four themes or factors regarding perceptions of citizens were identified: generally negative perceptions with regard to skills and competencies, work ethics, cultural disposition, and perceived effectiveness of Emiratisation. Research limitations/implications - The sample was not ideally balanced as it included more citizens compared to the overall composition of the labour market. Practical implications - The implications of these negative stereotypes on intergroup relations and expected impacts on Emiratisation are discussed. Ultimately, this paper provides a new subject perspective on immigration, presenting the case of citizens being a minority in need of acculturation to their own country's work environment. Originality/value - This paper is the first to empirically assess stereotyping and negative perceptions of citizens and its implications on workforce nationalisation in the GCC region. [PUBLICATION ABSTRACT]